Asthma-chronic obstructive pulmonary disease overlap syndrome - literature review and contributions towards a portuguese consensus - Araújo, D. (2021)
Introduction: Phenotypic overlap between the two main chronic airway pulmonary diseases, asthma and chronic obstructive pulmonary disease (COPD), has been the subject of debate for decades, and recently the nomenclature of asthma-COPD overlap syndrome (ACOS) was adopted for this condition. The definition of this entity in the literature is, however, very heterogeneous, it is therefore important to define how it applies to Portugal. Methods: A literature review of ACOS was made in a first phase resulting in the drawing up of a document that was later submitted for discussion among a panel of chronic lung diseases experts, resulting in reflexions about diagnosis, treatment and clinical guidance for ACOS patients.